Comparative Analysis of Efficacy and Complications after Unilateral Biportal Endoscopic Discectomy and Interlaminar Microdiscectomy - Balan, V.S.; Fishchenko, Ia.V.; Kravchuk, L.D.; Yachnik, S.P. (TERRA ORTHOPAEDICA, 2025)
Summary. To date, existing literature, including systematic reviews and meta-analyses, has demonstrated successful clinical outcomes with low complication rates for endoscopic biportal discectomy. However, these studies are limited, and quite a few similar studies have been covered in the scientific space in Ukraine, which highlights the need for further research in this direction. Objective. The objective of our study was to conduct a comparative analysis of treatment outcomes and complications after unilateral biportal endoscopic discectomy and interlaminar microdiscectomy in the treatment of herniated intervertebral discs of the lumbar spine. Material and Methods. The study was conducted at the Department of Neurosurgery of the Spine and Spinal Cord of the Ivano-Frankivsk Regional Clinical Hospital from May 2021 to June 2023. The sample included 276 patients with herniated intervertebral discs of the lumbar spine, divided into two groups according to the type of intervention: unilateral biportal endoscopic discectomy (n=159) and interlaminar microdiscectomy (n=117). Results. The results of our study showed that the severity of back pain after 1 month was lower in the endoscopic discectomy group compared to the interlaminar microdiscectomy group; however, after 6 months, the differences were not statistically significant (p > 0.05). Intergroup comparison revealed no significant differences in the manifestations of pain syndrome in the leg at both 1 month (t St = 1.65 at t Cr =1.98, p > 0.05) and 6 months (t St = 1.88 at t Cr =1.98, p > 0.05). The duration of surgery was on average shorter when using endoscopic access compared to interlaminar microdiscectomy (р ≤ 0.01), and blood loss was reduced by 63.1% during endoscopic access (p < 0.001). No significant differences in intraoperative complications were observed between the methods; among postoperative complications, cases of paresthesia were observed more often in the interlaminar microdiscectomy group (42 cases, 35.8%) compared to the unilateral biportal endoscopic discectomy group (28 cases, 17.6%) (p < 0.05). Conclusions. Our study revealed no differences between interlaminar microdiscectomy and unilateral biportal endoscopic discectomy in terms of the number of intraoperative complications (except for postoperative paresthesia). Similarly, the duration of hospital stay was shorter in the groups where endoscopy was used.